Social Self-Efficacy and their Relationship to Emotional Disorders among a Sample of Yarmouk University Students - Yousef Al-Sooud (My University, 2016)
This study aimed to reveal the social- self efficacy and their relationships to some emotional disorders among a sample of Yarmouk university students. The sample of the study consisted of (500) male and female students from Yarmouk students distributed on various disciplines and levels of study, were selected randomly. To achieve the objectives of the study, the researcher used of social – self efficacy scale was developed by (Fan & Mak 1998), and a list of symptoms (SCL-90-R) codified by Al-Shrefeen and Al-Shrefeen (2012). The results of the study showed that the level of social- self efficacy among of Yarmouk University students came with moderate degree. The results indicated that there was statistically significant negative relationship between the level of social – self efficacy, and emotional disorders, and the results showed that there was no difference in the strength of correlation between the level of social – self efficacy, and every disorder of emotional disorders, due to the different variable gender.

هدفت هذه الدراسة إلى الكشف عن الفاعلية الذاتية الاجتماعية وعلاقتها ببعض الاضطرابات الانفعالية لدى عينة من طلبة اليرموك. تكونت عينة الدراسة من (500) طالباً وطالبةً من طلبة جامعة اليرموك للفصل الدراسي الأول للعام الدراسي 2013-2014، منهم (239) طالباً، و(261) طالبة، تم اختيارهم بالطريقة العشوائية. ولتحقيق أهداف الدراسة، تم استخدام مقياس الفاعلية الذاتية الاجتماعية المطور من قبل فان وماك (Fan & Mak, 1998)، وقائمة الأعراض المرضية (SCL-90- R) المقننة من قبل الشريفين والشريفين (2012). أظهرت نتائج الدراسة أن مستوى الفاعلية الذاتية الاجتماعية لدى طلبة جامعة اليرموك جاء بدرجة متوسطة. وأشارت النتائج إلى وجود علاقة سالبة ذات دلالة إحصائية بين مستوى الفاعلية الذاتية الاجتماعية وكل اضطراب من الاضطرابات الانفعالية، كما بينت النتائج عدم وجود اختلاف في قوة العلاقة الارتباطية بين مستوى الفاعلية الذاتية الاجتماعية وكل اضطراب من الاضطرابات الانفعالية يعزى لاختلاف متغير الجنس.
الفاعلية الذاتية الاجتماعية وعلاقتها بالاضطرابات الانفعالية لدى عينة من طلبة جامعة اليرموك